Pemanfaatan Avatar Untuk Mengatasi Kecemasan Berbicara di Depan Umum Secara Online Pada Mahasiswa Fakultas Psikologi Universitas Negeri Makassar - Magfira Diah Lestari; Nurfitriany Fakhri; Irdianti Irdianti (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Public speaking anxiety is a psychological phenomenon commonly experienced by university students, particularly in online learning contexts. With the advancement of digital technology, one alternative strategy to address online public speaking anxiety is the use of avatars in virtual meetings, especially on platforms such as Zoom. This study aimed to examine the effectiveness of avatar utilization in reducing online public speaking anxiety among university students. A true experimental method was employed using an alternative-treatment design. The participants consisted of 15 female undergraduate students from the Faculty of Psychology, Universitas Negeri Makassar, class of 2023. Participants were randomly assigned into three experimental groups based on avatar representation: Actual Self, Other Self, and Ideal Self. Hypothesis testing was conducted using a t-test with a significance level of 0.05, analyzed with SPSS version 24.0 for Windows. The results indicated a significant reduction in public speaking anxiety in the Actual Self group, with a significance value of 0.01 (p < 0.05). These findings suggest that the use of avatars representing the actual self is effective in reducing online public speaking anxiety among psychology students. The study provides practical implications for students experiencing anxiety during online public speaking by highlighting avatar features as a potential coping strategy. Additionally, this research offers insights for educators and counselors in utilizing avatar-based approaches tailored to students’ characteristics, particularly in virtual meeting environments under specific conditions.